153 Novel Insights into the Pathophysiology of Hypertrophic Cardiomyopathy Using Label free Quantitative Proteomics. (31st May 2014) - Coats, Caroline; Mills, Kevin; Elliott, Perry
Abstract : Introduction: The genetic background of hypertrophic cardiomyopathy (HCM) is well described; however it fails to explain the phenotypic diversity characteristic of the disease. By performing an unbiased label-free quantitative proteomics analysis of heart tissue, we have identified important proteins and pathways that contribute to the cytoskeletal and metabolic alterations of HCM. To verify and validate these findings we have developed a targeted and rapid peptide-based tandem mass spectrometry (MS/MS) assay to prospectively screen a large genotyped cohort of patients. Methods: Heart tissue from 17 patients with HCM and 6 controls was homogenised and whole protein assayed, prior to tryptic digestion. Samples were analysed using PLGS Version 2.5 and quantified based on ion abundance using Progenesis LC-MS. Statistically significant differences were calculated by one-way ANOVA. Proteins were submitted for ontology and functional annotation bioinformatics. Selected differentially expressed proteins were validated in 59 patients by developing a targeted, high throughput, peptide-based multiple reaction monitoring (MRM) assay using a Waters Xevo TQ-S triple quadruple mass spectrometer. Further validation and localisation of proteins was confirmed with immunohistochemistry. Results: 1672 unique proteins were identified of which 152 were differentially expressed between the 2 groups (p < 0.05). Enriched protein groups included those involved in cytoskeletal protein binding and energy production. Novel findings included upregulation of Lumican, a small leucine-rich proteoglycan that controls the assembly of collagen fibres in the extracellular matrix. Myocardial lumican concentration was higher in 52 HCM (287 ± 24 pmol/l) patients than in 7 controls (132 ± 9 pmol/l) and highestin the sub-group of HCM patients (n = 17) with evidence of scarring on cardiac magnetic resonance imaging (302 ± 32 pmol/l). Conclusions: This is the first comprehensive global proteomic study of human hypertrophic cardiomyopathy. We have identified differences in the expression of several proteins in the HCM heart, many of which are relevant to the disease process. By developing a targeted and multiplexed MS/MS based assay we have been able to prospectively validate potential biomarkers in tissue, and create an assay that can be applied to screen plasma. Increased myocardial expression of Lumican is a possible marker of progressive disease in HCM.